Historical study in phonetics - Al-Zahrani, Saied (Arab Journal for Sciences and Research Publishing, 2017)
In the name of Allah, the Most Gracious the Most Merciful, and the prayer on his noble messenger, and on his family and companions and followers to the Day of Judgment. this research highlights the attention of the owners of each language sounds since ancient times, and perhaps one of the most important reasons that invited the Arabs, especially, to study them, it is our language the phonetics wasn’t known as this name for Arab until a late stage, Therefore, it did not go away from the works of the advanced Arab scholars in the towards them and their disbursement and communication and presentations and literary encyclopedias with their different arts. And other works such as medicine, wisdom and music, especially the work of sounds and melody, reading and recitation intensively, all these sciences touch the sound of the side can be mixed these different sciences in the sound so as not to fall on a book is devoid of words in the science of sounds or effects. Therefore, we will follow the nations that dealt with the science of sounds in our research by investigating and knowing the roles played by each nation separately, hoping to reach in this research to the integration of the role of each nation in the science of sound for the treatment of speech disorders or to adjust some similar letters that may be difficult for many languages learners. However, these studies in Arabic or other languages were not in isolation from that progress in science in general. Therefore, there was a coefficient of language that taught phonetics and dealt with the deficiencies of those who needed it. The study of all the nations that dealt with the sounds and their development was not successive and sequentially intertwined. The observation of the evolution of this science in its various aspects was not sudden, but it was varied and varied in each nation according to the interest of its people in that science and its care.